A instalaçao do pólo hemofarmo de Pernambuco: transformações territoriais e desenvolvimento - Barboza, Michel Saturnino (2012)
The objective is to analyze the implementation process of the Polo Hemofarmo of Pernambuco in critical perspective, identifying important alternatives to collaborate for the deployment of this enterprise, from the insertion of technological innovations and Public Policy generate different dynamics of the productive chain of Pharmacology in their different scales. The dialectical method in the development of procedures for the construction of Pole Hemofarmo demonstrated significant in the analysis, however, is not present in the proposed methodology of this study a methodological constraint and, yes, a discussion and reflection on the method of analysis. For a better understanding of the installation of the pole of Goiana held a reading scenario of the pharmaceutical industry and the sectors that constitute complementary and supplementary practices at the Pole, enabling identification of the technological demands and the new arrangements and policies, in Goiana, as well as the state of Pernambuco.